2012
DOI: 10.12659/msm.883604
|View full text |Cite
|
Sign up to set email alerts
|

The role of orthodontic tooth movement in bone and root mineral density: A study of patients submitted and not submitted to orthodontic treatment

Abstract: SummaryBackgroundOrthodontic force application to the teeth is responsible for a series of biological responses in the bone and dentin, which lead to some alterations of the mineral density of the tissues. Our objective was determine, through cone-beam computed tomography (CBCT), the mineral density of the apical third of the roots of the upper central incisors and of the periapical bone portion surrounding these teeth, in patients submitted to orthodontic treated and untreated individuals.Material/Methods30 u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 35 publications
1
9
1
5
Order By: Relevance
“…In addition to conducting mouse model experiments, several scholars have also used dental CBCT to measure the alveolar bone densities of orthodontic patients. Campos et al 26 compared the bone mineral densities (BMDs) and root mineral densities (RMDs) of 30 untreated persons and 15 patients who had completed their orthodontic treatment. The results revealed that the RMDs of the 15 patients were reduced, but their BMDs were similar.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to conducting mouse model experiments, several scholars have also used dental CBCT to measure the alveolar bone densities of orthodontic patients. Campos et al 26 compared the bone mineral densities (BMDs) and root mineral densities (RMDs) of 30 untreated persons and 15 patients who had completed their orthodontic treatment. The results revealed that the RMDs of the 15 patients were reduced, but their BMDs were similar.…”
Section: Discussionmentioning
confidence: 99%
“…Some previous studies on the effect of orthodontic treatment on changes in alveolar bone density have indicated that orthodontic tooth movement can decrease bone density around the teeth, 19 , 21 23 whereas others have reported the opposite. 21 , 24 , 25 Campos et al 26 indicated that bone density around the teeth following orthodontic treatment is similar to that from before treatment. Thus, research results regarding the effect of orthodontic treatment on bone density around the teeth have been inconsistent.…”
Section: Introductionmentioning
confidence: 96%
“…Thus, CBCT has been proposed as a diagnostic method for the determination of bone mineral density [10,11,18,[34][35][36] . Gray values obtained with CBCT are used in an analog way as the HU values for the determination of mineral density [16] and show a linear relationship with the attenuation coefficients of the materials [13,15] , HU values obtained with medical CT [11,12,37,38] , and density values from DEXA [14] .…”
Section: Cone Beam Ctmentioning
confidence: 99%
“…It is often thought that alveolar bone remodeling follows orthodontic tooth movement. Retracted teeth move through the alveolar bone, causing bone remodeling to occur with potential change in bone density and thickness to adapt to its new position [1][2][3]. Premolar extraction and orthodontic correction have been shown to be very effective in reducing dental protrusion in many studies [4].…”
Section: Introductionmentioning
confidence: 99%